The Leadership Of Islamic Education And Its Impact On Improving Teacher Performance At Mis Muhammadiyah Cijambe Garut West Java - Pancawati, Anita; Kusnadi, Cici (Tartib: Jurnal of Educational Management, 2025)
This research aims to explore the influence of Islamic educational leadership on improving teacher performance at MIS Muhammadiyah Cijambe, Cikelet District, Garut Regency, West Java. The study utilizes a qualitative approach to understand the key factors within Islamic leadership that contribute to the enhancement of teachers' professional performance. Data was collected through in-depth interviews with school leaders, teachers, and staff, along with direct observations and document analysis. The findings reveal that the implementation of Islamic leadership principles, such as role modeling, empowerment, and effective communication, significantly impacts teacher motivation, engagement, and overall performance. Islamic leadership, which emphasizes spiritual guidance, moral integrity, and community-based collaboration, has created a positive work environment, fostering greater teacher responsibility and accountability. Furthermore, it was found that supportive leadership practices contribute to improving teacher competency and effectiveness in the classroom. This research underscores the importance of integrating Islamic leadership values in educational settings to promote a conducive learning environment and enhance teacher performance.